Biomarker analyses and final overall survival results from a phase III, randomized, open-label, first-line study of gefitinib versus carboplatin/paclitaxel in clinically selected patients with advanced non - small-cell lung cancer in Asia (IPASS) - Fukuoka M. (2017)
Purpose: The results of the Iressa Pan-Asia Study (IPASS), which compared gefitinib and carboplatin/paclitaxel in previously untreated never-smokers and light ex-smokers with advanced pulmonary adenocarcinoma were published previously. This report presents overall survival (OS) and efficacy according to epidermal growth factor receptor (EGFR) biomarker status. Patients and Methods: In all, 1,217 patients were randomly assigned. Biomarkers analyzed were EGFR mutation (amplification mutation refractory system; 437 patients evaluable), EGFR gene copy number (fluorescent in situ hybridization; 406 patients evaluable), and EGFR protein expression (immunohistochemistry; 365 patients evaluable). OS analysis was performed at 78% maturity. A Cox proportional hazards model was used to assess biomarker status by randomly assigned treatment interactions for progression-free survival (PFS) and OS. Results: OS (954 deaths) was similar for gefitinib and carboplatin/paclitaxel with no significant difference between treatments overall (hazard ratio [HR], 0.90; 95% CI, 0.79 to 1.02; P = .109) or in EGFR mutation - positive (HR, 1.00; 95% CI, 0.76 to 1.33; P = .990) or EGFR mutation - negative (HR, 1.18; 95% CI, 0.86 to 1.63; P = .309; treatment by EGFR mutation interaction P = .480) subgroups. A high proportion (64.3%) of EGFR mutation - positive patients randomly assigned to carboplatin/paclitaxel received subsequent EGFR tyrosine kinase inhibitors. PFS was significantly longer with gefitinib for patients whose tumors had both high EGFR gene copy number and EGFR mutation (HR, 0.48; 95% CI, 0.34 to 0.67) but significantly shorter when high EGFR gene copy number was not accompanied by EGFR mutation (HR, 3.85; 95% CI, 2.09 to 7.09). Conclusion: EGFR mutations are the strongest predictive biomarker for PFS and tumor response to first-line gefitinib versus carboplatin/paclitaxel. The predictive value of EGFR gene copy number was driven by coexisting EGFR mutation (post hoc analysis). Treatment-related differences observed for PFS in the EGFR mutation - positive subgroup were not apparent for OS. OS results were likely confounded by the high proportion of patients crossing over to the alternative treatment. © 2011 by American Society of Clinical Oncology.